On‐site treatment of oral ulcers caused by cheek biting: A minimally invasive treatment approach in a pediatric patient - Vo Truong Nhu Ngoc; Luong Minh Hang; Hoang Van Bach; Dinh‐Toi Chu (Clinical Case Reports, 2019)
Key Clinical Message In small children, it would be desirable for oral lesions, especially on the symmetrical sides, to be screened carefully, and for treatment to begin with minimal interventions including on‐site medication and remedies to discontinue the bad routine. Minimal invasive approach and differential diagnosis are considered to be the main solutions for oral ulcers in pediatric patients.